Poeta i pedagog Józef Czechowicz o edukacji czytelniczej młodzieży - Uljasz, Adrian (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
The presented publication is a critical edition of the article by the poet and pedagogue Józef Czechowicz (1903 – 1939) entitled „Liryka i młodzi” (Poetry and the young) published in the third issue of the „Ogniwo” (“Link”) journal from 1933. This article was not included in the volumes with journalistic writings by Czechowicz. However, it deserves interest partially due to its always current contents. The author’s view on the necessity to adjust the programme of literary education and the book collections of public and school libraries to the reading interests of the youth should be shared by teachers and librarians at contemporary times similarly to the times when Czechowicz published his statement.
Poet and pedagogue Józef Czechowicz on reading education of the youth
Keywords: Czechowicz Józef (1903–1939); journalism; literary education; reading education; publicystyka; kształcenie literackie; edukacja czytelnicza